Avaliação qualitativa de um serviço de emergência psiquiátrica no hospital geral - Buriola, Aline Aparecida (2015)
In Brazil, in agreement with the Ministry of Health, 3% of the population is assisted with serious or severe mental illness and; more than 12% need assistance in Mental Health Services in a continuous or fortuitous manner. Considering such expressive data, it is important to carry out studies related to the dynamics of assistance on the units of care, so that those Services are recognized in the public health politics as appropriate structures to assist the emergent psychiatric demand in the country. Thus, the present research had the main purpose to evaluate a Psychiatric Emergency Service, which was part of a general hospital. An evaluative, qualitative, case study type research was accomplished, using as theoretical and methodological base, the Fourth Generation Evaluation, constructivist, responsive and with hermeneutic-dialectic approach. In the study, took part members of three interest groups: professionals (15), users (9) and relatives (6). Data was collected from February to June 2014, through non participant observation, participant observation and individual interview. The analysis of the material was accomplished by the constant comparative method. The interviews were transcribed verbatim and to obtain the results, the information referring to the empiric analysis, were associated to each group of interest and divided into thematic units; units of information and; fragments of interviews. For the consensus concerning the evaluation of the Service, the results were presented in negotiation meetings, with each group of interest. It was found that the Unit of Psychiatric Emergency presents a dynamics of assistance compromised by the high number of assistances. However, even with its capacity of assistance surpassed, the Psychiatric Emergency is able to promote humanized health assistance. With regard to the physical structure, it was possible to verify that the investigated health unit presents appropriate physical environment for the adults' immediate assistance. However, there is a necessity to adapt the quantitative of human resources and the physical structure which was not planned for the children's assistance. Concerning the nurse performance it was possible to apprehend that, even with accumulation of activities, the nurse role is essential in the organization of the assistance, as well as for the articulation between the multidisciplinary team and the care. It was concluded that, in the investigated Psychiatric Emergency Service the construction of care in mental health, in the pattern of the Psychiatric Reform, is still a challenge to be overcome, since it was proved that the quality of the care has been harmed due to the high demand of assistance; the physical structure for the assistance to children is inadequate and; there is an excessive load of work on the nurses.